The Use of Technology Acceptance Model to Explain Brand Attitude and Loyalty Intention in E-Commerce: The Gamification Case - Sari, Nadia N (UI Scholars Hub, 2022)
Manuscript type: Research Article Research Aims: This paper analyzes the role of the Technology Acceptance Model (TAM), perceived enjoyment, perceived social influence, consumer intention to engage, and brand loyalty in the context of gamification in e-commerce. Design/methodology/approach: Online survey was conducted to collect data, and Partial Least Square (PLS) was used to analyze the effects among variables. Research Findings: The study found that perceived usefulness, perceived social influence, and perceived enjoyment had a positive effect on brand attitude, while perceived ease of use had an insignificant effect on brand attitude. The brand attitude was found to have a significant effect on loyalty intention. Theoretical Contribution/Originality: This research elaborated on the role of TAM in using the gamification method for intention to engage, brand attitude, and its effect on loyalty intention. Practitioner/Policy Implication: The company that applies gamification should develop a fun and interesting game to create engagement. Emotional bonding and a positive consumer feeling must be maintained to build consumer loyalty. Research limitation/Implications: The external factor such as subjective norm, design, image, job relevance, technology efficacy influence, the level of perceived usefulness, and ease of use. Keywords: Technology Acceptance Model (TAM), perceived enjoyment, perceived social influence, brand loyalty, gamification, e-commerce.